PUSAT OLEH-OLEH DI OBJEK WISATA PANTAI TAKISUNG - Febrianty, Nurmelia; Huzairin, Muhammad Deddy (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
Takisung Beach is one of the most popular tourist destinations in Tanah Laut Regency. To meet the demand of tourists visiting Takisung Beach, The Department of Tourism and Culture of Tanah Laut Regency provides several supporting facilities. One of the supporting facilities provided is in the form of a souvenir market filled with local products. The existing souvenir market has an unfavorable condition, it is influenced by factors of cleanliness, spatial arrangement, and poor humidity for the convenience of visitors. Departing from this problem, a design project in the form of a souvenir center at Takisung beach was initiated which applies the concept of a relationship that functions to accommodate buying and selling activities for tourists. The concept of coastal architecture is applied by adjusting the design to the climate of the coastal environment using the bioclimatic method.